Lymph Node Abscessation Secondary to Neoplasia in Two Dogs. (26th March 2022) - Close, Erin; Lumbrezer-Johnson, Sarah; Hostnik, Eric; Burge, Rhonda; Jennings, Ryan; Selmic, Laura
Abstract : A 5-year-old male neutered mixed breed dog and an 8-year-old female spayed golden retriever presented for cervical swelling which was later diagnosed as abscessation of the retropharyngeal lymph node with a malignant round cell tumor and carcinoma with multifocal squamous differentiation, respectively. In veterinary medicine, there is limited published information regarding abscessation of lymph nodes secondary to a neoplastic process. While more common in humans, there are only limited case reports available. Advanced imaging (computed tomography), cytology, surgical excision, and histopathology lead to the final diagnosis. Both dogs underwent surgical extirpation of the lymph nodes and adjuvant chemotherapy protocols. Six weeks postsurgical excision, dog one was euthanized due to quality-of-life concerns. The second dog successfully completed 18 treatments of radiation therapy and was still alive at 388 days postsurgical excision. At the time of manuscript submission, the second dog was doing well clinically.